Intraoperative acidosis and hypercapnia during thoracoscopic repair of congenital diaphragmatic hernia and esophageal atresia/tracheoesophageal fistula. Issue 8 (20th June 2017) - Zani, Augusto; Lamas‐Pinheiro, Ruben; Paraboschi, Irene; King, Sebastian K.; Wolinska, Justyna; Zani‐Ruttenstock, Elke; Eaton, Simon; Pierro, Agostino
Summary: Background: Intraoperative hypercapnia and acidosis have been associated with thoracoscopic repair of both congenital diaphragmatic hernia and esophageal atresia/tracheoesophageal fistula. Aim: The aim of the present study was to investigate whether thoracoscopic repair of congenital diaphragmatic hernia or esophageal atresia/tracheoesophageal fistula was associated with acidosis and hypercapnia in a large group of neonates, and to analyze the effects of acidosis and hypercapnia on early postoperative outcomes. Methods: We reviewed the charts of neonates who underwent open or thoracoscopic congenital diaphragmatic hernia or esophageal atresia/tracheoesophageal fistula repair (2004‐2014). Patients with available intraoperative arterial gas values were included. Data (PaCO2 : mm Hg) were compared using paired/unpaired tests and are reported as difference [95% confidence interval]. Results: Congenital diaphragmatic hernia: 187 neonates underwent open (n=153) or thoracoscopic (n=34) repair. Intraoperative arterial gas values were recorded in 96 open and in 23 thoracoscopic operations. Both groups had similar preoperative pH and PaCO2, and developed intraoperative acidosis (open −0.08 [−0.11, −0.05] P <.001, thoracoscopic −0.14 [−0.24, −0.04] P =.01) and hypercapnia (open: 7.8 [3.2, 12.4], P =.002; thoracoscopic: 20.2 [−2.5, 43, P =.07). Intraoperatively, neonates undergoing thoracoscopic repair developed lower pH than those having open surgery (−0.06 [−0.01, −0.10] P =.018), but maintained similar levels of PaCO2 (−4.0 [−9.0, 4.4] P =.39). Esophageal atresia/tracheoesophageal fistula: 205 neonates underwent open (n=180) or thoracoscopic (n=25) repair. Intraoperative arterial gas values were recorded in 62 open and in 14 thoracoscopic operations. Both groups had similar preoperative pH and PaCO2, and developed intraoperative acidosis (open: −0.09 [−0.14, −0.04], P <.001; thoracoscopic: 0.21 [−0.28, −0.14], P <.001) and hypercapnia (open: 9.2 [2.6, 15.7] P =.008; thoracoscopic: 15.2 [1.6, 28.7], P =.03). Intraoperatively, neonates undergoing thoracoscopic repair developed lower pH than those having open surgery (difference 0.08 [0.01, 0.15], P =.02) but maintained similar levels of PaCO2 (difference −1 [−9, 3], P =.35). Conclusion: Neonates undergoing operative repair of congenital diaphragmatic hernia and esophageal atresia/tracheoesophageal fistula develop intraoperative acidosis and hypercapnia, regardless of the approach used. However, this phenomenon is more severe during thoracoscopic repair. Novel modalities to reduce intraoperative gas derangements, particularly during thoracoscopic repair, need to be established.